Penggunaan Metode Amtsilati untuk Meningkat Kemampuan Membaca Kitab Kuning Siswa - Ridwan, Iwan; Suaidi, Suaidi; Hidayat, Samsul (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2022)
This study aims to determine: (a) how the Amtsilati method in the Takhossus class of SMPS Riyadhul Mubtadiin Cimanuk Pandeglang, (b) How is the application of the Amtsilati method to the ability to read the yellow book of students in the Takhossus class of SMPS Riyadlul Mubtadiin Cimanuk Pandeglang, (c) Is there any influence from the application of the method Amtsilati in the Nahwu Shorof class of students in the Takhossus class of SMPS Riyadlul Mubtadiin Cimanuk Pandeglang. The location of this research is at SMPS Riyadlul Mubtadiin Cimanuk Pandeglang. The method used in this research is a qualitative method in the form of classroom action research (CAR). The method of data collection was done by interview and observation. The results of this study indicate that the amtsilati method is a new breakthrough to make it easier for students to be able to read the yellow book in a relatively short period of time (3 to 6 months), and this method is packaged so attractively and practically so that it is easy to learn, even for children who are as young as possible. The advantage of the amtsilati method is that it is easy to understand by all people, even children, on the condition that people who learn amtsilati can read Arabic script and can read alphabetic writing. Because the core book of amtsilati, namely the book of qoidati, uses Indonesian and the examples use Arabic because most of the examples are quoted from the Qur'an.